Teachers as Safeguards: An Analysis of Teachers' Attitudes Towards Child Sexual Abuse - Liza Fidiawati; Safriatullah Safriatullah; Cut Fazlil Hanum; Amelia Putri; Nova Trisnanda (Bulletin of Counseling and Psychotherapy, 2025)
Child sexual abuse is a serious problem that has a significant impact on child development and protection, making teachers' attitudes as protectors in the school environment crucial. However, research examining the psychological factors that shape teachers’ attitudes toward child sexual abuse, particularly in the context of developing countries, remains limited and fragmented. This study aims to analyse the influence of teachers' attitudes toward child sexual abuse, specifically examining the role of anxiety, trust, and commitment in shaping these attitudes. The method used was a quantitative survey design. The research sample consisted of 307 kindergarten teachers in Banda Aceh City, Indonesia, randomly selected and stratified by length of work experience. The instrument used was the Teachers' Attitudes Toward Reporting Child Sexual Abuse, which consists of 21 items with a five-point Likert scale, divided into three main factors: anxiety, trust, and commitment. Data were analysed using multiple regression to measure the influence of independent variables on teachers' attitudes as the dependent variable. The results showed that teachers' commitment and trust significantly strengthened proactive attitudes in preventing and addressing child sexual abuse, while anxiety had a negative effect.